Design of a 3-DOF Parallel Manipulator to Compensate for Disturbances in Facade Cleaning - Garam Park (IEEE Access, 2020)
This paper proposes a three-degree-of-freedom manifold composed of three linear actuators. The proposed mechanism consists of a workspace suitable for facade cleaning and can compensate for the horizontal position from disturbances in a gondola-based exterior-wall cleaning. We design a cleaning manipulator that can ensure a constant cleaning area by compensating for the disturbance in each direction. The position, velocity kinematic, and Jacobian-based singularity analysis are presented, and kinematic variables are defined to extend a singularity-free workspace. In addition, optimization is performed based on an index that demonstrates the mechanical properties of the manipulator. The result shows how the manipulator compensates for the disturbances as well as the features of the optimization model. This study can be applied to robot manipulators for facade cleaning in the future.